Design and Development of an Off-Grid Solar Power Monitoring System on A 160 Wp PV System at SMPN 04 Tempurejo, Jember Regency - Ramadhan, Fila; Rachmanita, Risse Entikaria; Mulyono, Novangga Adi; Nurazaq, Warit Abi; Hasbiyati, Haning (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Solar energy can be converted into electrical power through photovoltaic (PV) technology, commonly referred to as solar panels. As a result, the implementation of a monitoring system is crucial to mitigate battery degradation caused by excessive discharging. This study employs a research and development (R&D) approach. The off-grid solar power monitoring system installed at SMPN 04 Tempurejo is designed to facilitate maintenance and enhance system reliability. By integrating Internet of Things (IoT) technology, the monitoring system allows for real-time tracking of voltage, current, and power output from the PV system via smartphone access, irrespective of location. Consequently, the IoT-based monitoring system significantly improves the management and oversight of the off-grid solar power system at SMPN 04 Tempurejo.